This brave new world : India, China and the United States - Manuel, Anja. (New York, NY : Simon & Schuster, 2016)
"In the next decade and a half, China and India will become two of the world's indispensable powers--whether they rise peacefully or not. During that time, Asia will surpass the combined strength of North America and Europe in economic might, population size, and military spending. Both India and China will have vetoes over many international decisions, from climate change to global trade, human rights, and business standards. From her front row view of this colossal shift, first at the State Department and now as an advisor to American business leaders, Anja Manuel escorts the reader on an intimate tour of the corridors of power in Delhi and Beijing. Her encounters with political and business leaders reveal how each country's history and politics influences their conduct today. Through vibrant stories, she reveals how each country is working to surmount enormous challenges--from the crushing poverty of Indian slum dwellers and Chinese factory workers, to outrageous corruption scandals, rotting rivers, unbreathable air, and managing their citizens' discontent. We wring our hands about China, Manuel writes, while we underestimate India, which will be the most important country outside the West to shape China's rise. Manuel shows us that a different path is possible--we can bring China and India along as partners rather than alienating one or both, and thus extend our own leadership in the world"--
"The US has the power to shape the geopolitical future of this century. We must stop obsessing about China alone and actively encourage India's enormous potential to balance China's power. India, China, and the US will be the twenty-first century's dynamic triumvirate. The axial shift of world power from the United States and Europe to China and India is unrelenting. By 2030, intelligence agencies estimate that Asia will surpass the combined power of North America and Europe in economic might, population size, and military spending. From a front row seat Anja Manuel argues and demonstrates that India has the assets and structure to grow democratically to full strength and balance the Chinese hegemony and aggression while it takes its proper place in leadership with India and the US. In This Brave New World, Manuel takes the reader along on her business trips as she meets leaders and counts the assets and deficiencies of the two giant countries. India has a youthful, English-speaking population and democratic traditions, but it is inefficient, misogynist, and often corrupt. China has an aging population, no tradition of citizen rule, an ideological central government, and is ruthlessly expansionist. India's democratic system slows it down; China's centralized authority races it erratically. Balancing these giants is the key to a prosperous and open global system and America's opportunity to maintain its world power. In the present and near future the US's aim should be to embrace the inevitable rise of India and China and with them continue to lead the global governance. We must stop our handwringing about China's rise and focus instead, warns Manuel, on forging harmonious relationships with both giants, to create this brave new world"--
Includes bibliographical references (pages 293-339) and index.
Keywords: United States -- Foreign relations -- India; India -- Foreign relations -- United States; United States -- Foreign relations -- China; China -- Foreign relations -- United States; World politics -- 21st century; Estados Unidos -- Relaciones exteriores -- India; India -- Relaciones exteriores -- Estados Unidos; Estados Unidos -- Relaciones exteriores -- China; China -- Relaciones exteriores -- Estados Unidos